2021
DOI: 10.2478/ijhp-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Current practice of physical therapists in outpatient stroke rehabilitation: a cross-sectional survey in Baden-Württemberg and Thuringia / Arbeitsweise von Physiotherapeut*innen in der ambulanten Schlaganfallrehabilitation: eine Querschnittsumfrage in Baden-Württemberg und Thüringen

Abstract: Objective Guidelines recommend task-oriented training and the use of standardized assessments to improve stroke-related mobility deficits. However, the German outpatient physical therapy prescription catalogue does not include these recommendations resulting in a possible gap between guideline recommendations and clinical practice. Therefore, the purpose of this study was to describe physical therapy practice patterns of stroke-related mobility deficits in the outpatient setting exemplified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
2
0
1
Order By: Relevance
“…Previous systematic reviews have identified multiple measures of sitting balance used for people after stroke (90), with over 60 different measures of standing balance in the adult population (69), and over 30 measures of mobility for older adults (91). We found that the assessment tools included in at least 70% of CPGs (i.e., BBS, 6MWT, TUG, and 10mWT) are consistent with the tools most frequently used in clinical practice as indicated by clinician surveys conducted in Canada (92)(93)(94), Colombia (95), Ghana (27), and Germany (32). Moreover, our analyses considering CPGs by country income level showed that the BBS, 6MWT, TUG, and 10mWT, are currently recommended by CPGs from middle-and high-income countries.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Previous systematic reviews have identified multiple measures of sitting balance used for people after stroke (90), with over 60 different measures of standing balance in the adult population (69), and over 30 measures of mobility for older adults (91). We found that the assessment tools included in at least 70% of CPGs (i.e., BBS, 6MWT, TUG, and 10mWT) are consistent with the tools most frequently used in clinical practice as indicated by clinician surveys conducted in Canada (92)(93)(94), Colombia (95), Ghana (27), and Germany (32). Moreover, our analyses considering CPGs by country income level showed that the BBS, 6MWT, TUG, and 10mWT, are currently recommended by CPGs from middle-and high-income countries.…”
Section: Discussionsupporting
confidence: 68%
“…The use of standardized assessment tools in physical therapy practice is inconsistent (27)(28)(29)(30)(31)(32). Common barriers to the use of standardized assessment tools are lack of time, insufficient knowledge, lack of description of how to administer standardized assessment tools, and low perceived value of some instruments (24, 28,29,[31][32][33][34][35][36]. Additionally, the context in which PTs practice, such as the income level of a country, influences practice experiences (33).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Bezug auf die Gesundheitsfachberufe zählt Deutschland zu den Ländern mit einer relativ kurzen akademischen und wissenschaftlichen Tradition [22]. Dementsprechend zeigen aktuelle Ergebnisse aus Deutschland eine mäßige Umsetzung von EBP und leitlinienorientierter Therapie [23,24].…”
Section: Ebp Und Die Lücke Zwischen Forschung Und Praxisunclassified